Managerial ownership prediction model usinglogistics multinomial analysis technique - Triska Dewi Pramitasari; Isti Fadah; Hadi Paramu (Universitas Mercu Buana Yogyakarta, 2016)
Agency conflictoccurs because of the misalignment between the interests of managers and shareholders.Managerial ownership is one of the mechanisms used to minimize the occurrence of agency conflict.The greater managerial ownership in the company, the management will improve performance to achieve the interests of shareholders and its own interests.This study examines the factors that are used in predicting the managerial ownership that is dividend policy, debt policy, profitability, company size, investment opportunities, the company's value and the market value of equity.The sample in this study is LQ45 companies as many as 81 companies during the period 2011-2015, which were analyzed using multinomial logistic analysis to find out which of the seven independent variables that can be used to predict managerial ownership in the perspective of agency theory.The results of this study concluded that the dividend policy, debt policy and equity market value consistently affect managerial ownership prediction of medium and large categories, while profitability, company size, investment opportunities and the value of the company did not consistently affect the prediction of managerial ownership.